2020
DOI: 10.1140/epjst/e2019-900150-7
|View full text |Cite
|
Sign up to set email alerts
|

Transport signatures of Majorana bound states in superconducting hybrid structures

Abstract: In this minireview, we outline the recent experimental and theoretical progress in the creation, characterization and manipulation of Majorana bound states (MBSs) in semiconductor-superconductor (SC) hybrid structures. After an introductory overview of the broader field we specifically focus on four of our recent projects in this direction. We show that the emergence of Fano resonances in the differential conductance in a normal lead-Majorana nanowire-quantum dot setup can be exploited to determine if a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 202 publications
(291 reference statements)
0
13
0
Order By: Relevance
“…Majorana zero-modes have been intensively studied in recent years (see the research trend shown in Figure 1) owing to their potential application in fault-tolerant quantum computing. There have already been many review papers about Majoranas [1][2][3][4][5][6][7][8], mainly on Majorana theories. This review will briefly introduce recent experimental developments of one-dimensional Majorana devices, aiming to give a comprehensive overview and understanding of one-dimensional Majorana experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Majorana zero-modes have been intensively studied in recent years (see the research trend shown in Figure 1) owing to their potential application in fault-tolerant quantum computing. There have already been many review papers about Majoranas [1][2][3][4][5][6][7][8], mainly on Majorana theories. This review will briefly introduce recent experimental developments of one-dimensional Majorana devices, aiming to give a comprehensive overview and understanding of one-dimensional Majorana experiments.…”
Section: Introductionmentioning
confidence: 99%
“…MBS were predicted to naturally emerge in p-wave superconductors [1,9]. However, TS can also be engineered by using a conventional s-wave superconductor in proximity to a material with nontrivial spin structure, typically provided by spin-orbit coupling (SOC) [10][11][12][13][14][15][16][17] and/or magnetic textures [18][19][20][21][22][23][24][25][26]. The proximity induced superconductivity provides the necessary particlehole symmetry, while the SOC makes possible the realization of odd-in-momentum triplet pairing.…”
mentioning
confidence: 99%
“…These states are not only of tremendous interest for fundamental research, but also because their non-Abelian statistics makes them ideal building blocks for fault tolerant quantum computation [5][6][7]. Realizations [8][9][10][11][12] of topological superconductors hosting MBS are usually sought in materials with proximity-induced s-wave pairing and a nontrivial spin structure, typically provided by spinorbit coupling (SOC) and/or magnetic textures [13][14][15][16][17][18][19][20][21][22]. In the pursuit of topological superconductivity (TS), early experimental efforts have focused mostly on onedimensional (1D) systems such as hybrid structures of superconductors and semiconductor nanowires [8][9][10][11] or atomic chains [12].…”
mentioning
confidence: 99%